Analysis of Light Pollution as a Neglected issue in Development - Rika Isnarti (Universitas Potensi Utama, 2020)
The growth of economy that encourage development sometimes cause damage to environment. One of the case is light pollution while many people do not realize this pollution is existed. This research analyses light as one kind of pollution that people tend to unrealize. It describes cause and effect of light pollution. This pollution occurs because overused and misdirected light. Moreover, economics growth and increasing of population encourage this phenomena. Further, It argues that light pollution gives bad impact to environment and animal as well as becomes a threat to human health. This research employs qualitative methods by collecting, categorizing data from library research. It found that light pollution give bad impact to environment and human health, such as miss direction in migration animals, we cannot see Milky Way, and potential breast cancer to human. In addition, light pollution also wastes of energy. So, more attention has to be paid to this pollution and several managements in development and regulation have to be taken to manage this pollution worse. Keywords: